Facile and direct detection of human papillomavirus (HPV) DNA in cells using loop-mediated isothermal amplification (LAMP). (October 2021) - Vo, Dat T.; Story, Michael D.
Abstract: Human papillomavirus (HPV)-mediated cancers, particularly cervical and oropharyngeal cancer, lead to hundreds of thousands of deaths worldwide each year. Simple, straightforward, and cost-effective detection of HPV DNA from patients with these malignancies or at risk for developing cancer can improve outcomes for patients, serving as a tool for early detection, monitoring treatment response, and assessment of cancer recurrence. Loop-mediated isothermal amplification (LAMP) is a simple and robust method for the detection and amplification of DNA in a single tube, utilizing the Bst strand-displacing DNA polymerase. We developed a workflow utilizing LAMP for the visual detection of HPV DNA in oral rinses. We demonstrate that LAMP is able to easily discriminate between two of the high-risk HPV subtypes, HPV16 and HPV18. We then utilized LAMP to visually detect HPV DNA directly from cells in oral rinses, mimicking a clinical inspired scenario of detecting HPV DNA in clinical samples. Our results suggest that LAMP is a robust, colorimetric assay method for the detection of HPV DNA in complex cellular samples, and further development is warranted to bring LAMP into the clinic. Highlights: Human papillomavirus is the causative agent in many cancers, such as cervical cancer and oropharyngeal cancer. Detection of HPV DNA can have broad applications, such as in diagnosis, treatment monitoring, and evaluating for cancer recurrence. We describe a straightforward method for the detection of HPV DNA using loop-mediated isothermal amplification. This method is facile and inexpensive and can be implemented at the bedside with minimal equipment or technical expertise requirement.